2014
DOI: 10.1016/j.neuron.2014.08.001
|View full text |Cite|
|
Sign up to set email alerts
|

The Stimulus Selectivity and Connectivity of Layer Six Principal Cells Reveals Cortical Microcircuits Underlying Visual Processing

Abstract: SummarySensory computations performed in the neocortex involve layer six (L6) cortico-cortical (CC) and cortico-thalamic (CT) signaling pathways. Developing an understanding of the physiological role of these circuits requires dissection of the functional specificity and connectivity of the underlying individual projection neurons. By combining whole-cell recording from identified L6 principal cells in the mouse primary visual cortex (V1) with modified rabies virus-based input mapping, we have determined the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
198
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(222 citation statements)
references
References 79 publications
23
198
1
Order By: Relevance
“…Previous studies showed that L6 CT and CC neurons exhibit distinctive intrinsic properties, including excitability (Brumberg et al, 2003; Kinnischtzke et al, 2016; Kumar and Ohana, 2008; Velez-Fort et al, 2014; Yang et al, 2014), however the results of these studies differed substantially. Clarifying these differences is critical for understanding L6 circuit mechanisms.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies showed that L6 CT and CC neurons exhibit distinctive intrinsic properties, including excitability (Brumberg et al, 2003; Kinnischtzke et al, 2016; Kumar and Ohana, 2008; Velez-Fort et al, 2014; Yang et al, 2014), however the results of these studies differed substantially. Clarifying these differences is critical for understanding L6 circuit mechanisms.…”
Section: Resultsmentioning
confidence: 89%
“…Broadly speaking, three main types of L6 neurons can be defined by their axonal projections (Zhang and Deschenes, 1997): excitatory corticothalamic (CT) and corticocortical (CC) projection neurons, and local inhibitory interneurons. The L6 projection neurons differ in their intrinsic properties, dendrite and axon morphologies, long-range inputs and outputs, and in vivo activity patterns (Kumar and Ohana, 2008; Narayanan et al, 2015; Oberlaender et al, 2012; Velez-Fort et al, 2014; Yang et al, 2014); this has led to suggestions that L6 CT and CC cells participate in distinct subcircuits within the infragranular network (Kumar and Ohana, 2008; Velez-Fort et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…2). This has been done by either infecting neurons in the desired starter cell location with a Credependent helper virus (Figure 2; Wall et al, 2010; among many other publications cited previously), or by crossing the Cre driver line with a responder mouse line that has Cre-dependent expression of TVA and G (Li et al, 2013;Takatoh et al, 2013;Stanek et al, 2014;Bourane et al, 2015). Following adequate expression of the Cre-dependent gene products, EnvA ϩ RVdG is injected which, as described above, can result in selective infection of starter cells.…”
Section: Tracing Direct Inputs To Specific Cell Types Using Cre Linesmentioning
confidence: 99%
“…Published studies using monosynaptic RV tracing have described the connections to single neurons (Marshel et al, 2010;Rancz et al, 2011;Vélez-Fort et al, 2014), to cell types defined by their projection to particular locations (Stepien et al, 2010;Yonehara et al, 2011;Takatoh et al, 2013;Cruz-Martín et al, 2014;Levine et al, 2014;Ni et al, 2014;Sreenivasan et al, 2015), to cells targeted by their birth date (Arenkiel et al, 2011;Nakashiba et al, 2012;Vivar et al, 2012;Deshpande et al, 2013;Li et al, 2013;, to neurons with particular cell-surface receptors , and to genetically identified cell types in Cre-or tTA-expressing mouse lines (Haubensak et al, 2010;Weible et al, 2010;Watabe-Uchida et al, 2012;Fu et al, 2014;Kohara et al, 2014;Ogawa et al, 2014;Pollak Dorocic et al, 2014;Sun et al, 2014;. The results have led to novel insights into the relationships between the organization and function of neural circuits throughout the nervous system; from muscles or peripheral sensory receptors to the brain; and in nearly every neural system, from vision to motor function and neuromodulatory systems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, electroporation and targeted patching of single cells of interest in vivo to introduce TVA, followed by infection of the TVA-expressing cells with EnvA-pseudotyped rabies viruses, allows analysis of single neuronal networks with single-cell resolution. 147,157,158) The most striking feature of RABVΔG is that complementation of G in trans enables transsynaptic spreading of RABVΔG to directly-connected, presynaptic neurons 45,46,119,[147][148][149] (Figs. 4E, F).…”
Section: Rabies Virusesmentioning
confidence: 99%